Biomarkeri oksidativnog stresa i apoptoza hondrocita kao prediktori postoperativnih ishoda kod osteonekroze glave butne kosti: Oxidative Stress Biomarkers in ONFH Recovery - HU, CHIA-JUI; Song, Ming; Yu, Lai; Zeng, Guanfei (Journal of Medical Biochemistry, 2025)
Background: Osteonecrosis of the femoral head (ONFH) is a progressive disease where oxidative stress and chondrocyte apoptosis contribute to cartilage degeneration and postoperative complications. Identifying reliable biochemical markers is essential for prognosis after hip resurfacing arthroplasty (HRA). Methods: A retrospective analysis was conducted in 134 ONFH patients (ARCO stage II–III) treated with HRA. Serum oxidative stress markers—reactive oxygen species (ROS), superoxide dismutase (SOD), and malondialdehyde (MDA)—were measured preoperatively and at serial postoperative timepoints. Chondrocyte apoptosis rates were assessed by flow cytometry. Pain and functional recovery were evaluated using VAS and Harris hip scores. Correlation, univariate, and Cox regression analyses were applied to determine associations with postoperative outcomes. Results: Patients with high oxidative stress had significantly increased ROS and MDA levels, reduced SOD activity, and elevated chondrocyte apoptosis (P<0.05). These patients showed delayed functional recovery and higher complication rates. Strong correlations were observed between oxidative markers and apoptosis (ROS: r=0.912; MDA: r=0.901; SOD: r=−0.875). Cox regression identified ROS, MDA, reduced SOD, and apoptosis as independent risk factors for postoperative failure (HR range: 1.06–1.49, all P<0.05). Conclusion: Serum oxidative stress markers and chondrocyte apoptosis rates are closely linked to joint recovery and complications after HRA in ONFH patients. These biochemical indicators may serve as prognostic biomarkers, supporting early identification of high-risk individuals and guiding personalized postoperative interventions.